PENGARUH PENGGUNAAN BAHASA INDONESIA BERDASARKAN PEDOMAN EYD PADA MEDIA SOSIAL INSTAGRAM - Azra Hidayah Ramadani; Lutvia Andini Putri; Ranti Agathis Basri; Wahdini Saleha; Saptiana Sulastri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The purpose of this study is to find out various languages that are trending towards communication on social media, especially Instagram media. Data was collected to understand various information about language in modern times. Then the collected data was classified according to spelling errors from various slang languages. The research method used is a qualitative descriptive method. The author will describe the data obtained one by one. Based on the results of the study, namely along with the advancement of the times and technology, there are more and more choices of ways to communicate quickly, easily and practically. The conclusion that can be drawn in using Instagram social media is that the more the times develop, the more slang will appear. The use of new sentences requires correct language improvements to make them easy to understand.